Cystatin C Levels in Middle-Aged Patients with Obstructive Sleep Apnea Syndrome - Archontogeorgis, Kostas; Nena, Evangelia; Tsigalou, Christina; Voulgaris, Athanasios; Xanthoudaki, Maria; Froudarakis, Marios; Steiropoulos, Paschalis (Pulmonary Medicine, 2016)
Background. Obstructive sleep apnea syndrome (OSAS) is associated with systemic inflammation and increased risk of cardiovascular and chronic kidney disease. Cystatin C (Cyst C) is a novel biomarker of both latent renal damage and cardiovascular disease. Aim of the study was to measure serum levels of Cyst C, as well as IL-8 and CRP, in otherwise healthy OSAS patients. Methods. 84 individuals examined with polysomnography for OSAS symptoms without known comorbidities were prospectively recruited. Results. According to apnea hypopnea index (AHI) subjects were divided in two groups: OSAS group (AHI > 5/hour, n=64) and controls (AHI < 5/hour, n=20), which were age- and BMI-matched. Cyst C levels were higher in OSAS patients versus controls (1176.13±351.33 versus 938.60±245.83 ng/mL, resp.; p=0.017) while serum IL-8 and CRP levels did not differ significantly. Positive correlation was found between Cyst C levels and respiratory disturbance index (RDI) (r=0.240, p=0.039) and percentage of time with oxygen saturation <90% (r=0.290, p=0.02) and negative correlation was found between Cyst C levels and average oxygen saturation during sleep (r=-0.291, p=0.012). After adjustment for age and BMI, RDI was the only independent predictor of Cyst C levels (β = 0.256, p=0.039). Conclusion. Cyst C serum levels are increased in OSAS patients without comorbidities, suggesting an increased renal and cardiovascular disease risk.